THE ROLE OF BIOLOGICAL FLUIDS IN THE DEVELOPMENT OF KIDNEY STONE DISEASE - Raxmonov Baxrom Baxtiyor o'g'li (TADQIQOTLAR.UZ, 2024)
Abstract: The role of biological fluids, particularly urine, in the development of kidney stone disease is paramount to understanding its pathogenesis. This review delves into the dynamics of biological fluids, including their composition, physicochemical properties, and the balance of promoters and inhibitors of crystallization. It explores recent insights into the influence of urine pH, supersaturation levels, the impact of other bodily fluids, and emerging evidence on extracellular vesicles and the microbiome. The findings underscore the importance of modifying urinary composition through dietary and therapeutic measures to mitigate stone formation risk.